NEW AND PROMISING TRENDS IN THE PROCESSING OF DRIED GRAPES - Dehkanova Shakhnoza Yulbarsovna (Web of Journals Publishing, 2025)
The purpose of this work is to analyze chemical reactions.
Keywords: Chemical reaction, sodium, iron oxide.